Human recombinant factor IX: safety and efficacy studies in hemophilia B patients previously treated with plasma-derived factor IX concentrates - Roth, David A.; Kessler, Craig M.; Pasi, K. John; Rup, Bonita; Courter, Suzanne G.; Tubridy, Karen L. (Blood, 2001)
Human plasma–derived factor IX (pdFIX) concentrates are routinely used to treat patients with hemophilia B, an X-linked bleeding disorder that affects 1 in 30 000 males, but concerns remain regarding transmission of blood-borne pathogens. Therefore, the safety and efficacy of recombinant human factor IX (rFIX) were evaluated. A 20-center international trial was conducted in previously treated patients with severe or moderate (< 5 IU/dL factor IX activity) hemophilia B. Participants received rFIX for pharmacokinetic studies, treatment of or prophylaxis against hemorrhage, or surgical hemostasis, and were assessed at 3-month intervals for 2 years. Fifty-six subjects were treated. Mean incremental rFIX recovery was 0.75 IU/dL per IU/kg, 30% lower than expected for pdFIX, although the mean half-life was similar. Pharmacokinetic parameters were stable over time. Somewhat lower recoveries were seen in subjects younger than 15 years of age and in those with no detectable factor IX antigen. A total of 7362 infusions of rFIX were administered. All 1796 hemorrhages were controlled, 80.9% of which required only one rFIX infusion. Effective hemostasis was also achieved in prophylactic and surgical settings. One individual developed a low titer (1.2 Bethesda unit) transient inhibitor that spontaneously resolved. rFIX was not associated with serious adverse events, thrombogenicity, or virus transmission. rFIX is safe and effective for the treatment of hemophilia B. Despite a lower recovery compared with pdFIX, rFIX controlled hemorrhage in a wide variety of settings and may provide a safety advantage in terms of risk from blood-borne pathogens.